PENGARUH PERUNDUNGAN DAN KETIDAK HARMONISAN KELUARGA TERHADAP EMOSI ANAK BERKEBUTUHAN KHUSUS DI SLB B TUNAS KASIH 2 KOTA BOGOR - Cece Nasrudin (Jurnal PGSD, 2020)
Harrasment and disharmony are one of the factors that influence children’s emotions and in this case children with special needs. This study aims to examine and find out empirical data about the effects of abuse or bullying and family disharmony on the emotions of children with special needs separately or simultaneously. In this study, the authors used a survey method with a correlational approach to quantitative data obtained from the research object, namely parents of children with special needs SLB B Tunas Kasih 2, Bogor City. The total population is 44 students in the odd semester of the 2019-2020 school year. And taken a sample for research a total of 30 guardians of students. Data collection was carried out using a questionnaire. The type of analysis used is correlation and regression analysis which is described descriptively. The results of the study are: First, there is a positive and significant influence between Harassment or bullying on the Emotion of students in SLB B Tunas Kasih 2, Bogor. Secondly, there is a positive and significant influence between disharmony towards emotions in SLB B Tunas Kasih 2, Bogor. Third, there is a positive and significant influence between Harassment or Bullying and Disharmony together on the emotions of students in SLB B Tunas Kasih 2, Bogor which is indicated by the Probability value (Sig. F Change) = 0.00 smaller than 0.05 (0, 00 <0.05). The coefficient of determination (R2) is 79.7%. The shape of the effect is indicated by the regression equation Y = -4,303 + 0,395 X1 + 0,636 X2. Keyword: Harrasment/Bullying, Disharmony and Emotion